Gene Signatures and Prognostic Values of m6A Genes in Nasopharyngeal Carcinoma - Lu, Shanshan; Yu, Zhengzheng; Xiao, Zhiqiang; Zhang, Yiya (Frontiers in Oncology, 2020)
Nasopharyngeal carcinoma (NPC) is a malignant tumor with a high rate of local invasion and early distant metastasis. Accumulating studies suggests that 6-methyladenosine methylation (m6A) is closely related to tumorigenesis. However, the relationship between m6A related genes and prognosis of NPC is poorly understood. Our research aims to discover the prognostic value of m6A RNA methylation genes in NPC. In this study, we analyzed the differentially expressed m6A related genes between NPC samples and normal control samples, and found that two up-regulated genes (YTHDF3 and IGF2BP2) and one down-regulated gene (METTL3) were overlapped in GSE68799 and GSE53819. Next, we found that high expression of IGF2BP1 and low expression of METTL3 and YTHDF3 in NPC patients showed poor progression-free survival (PFS). Subsequently, the 4 m6A genes were selected for consensus cluster analysis and risk models were established. The risk signature, using three-gene (GF2BP1 + IGF2BP2 + METTL3), was an independent prognostic factors and predict the clinicopathological features of NPC. Additionally, the GO, KEGG analysis and CIBERSORT algorithm revealed that the risk signature was closely associated to immune infiltration in NPC. Finally, the expression and clinical significance of METTL3 were successfully validated in NPC tissues using immunohistochemical techniques. In conclusion, our ﬁnding revealed the potential role of m6A modification in NPC, providing novels insight into NPC prognosis and therapeutic strategies.